Aplikasi 2 Dimensi Pengenalan Negara Benua Asia Tenggara Untuk Sekolah Dasar Dengan Metode MDLC - Irfan Hadi; Putri Harliana; Khairunnisa (Unit Pengelola Jurnal Universitas Harapan Medan, 2022)
The development of information and communication technology today, makes the learning process can be doneanywhere and anytime, for example, android-based learning. With the existence of android-based learning media,it can generate student learning motivation and allow students to learn independently according to their abilitieswherever and whenever. The development of interactive learning media requires software development methods,one of the development methods that can be used is the Multimedia Development Life Cycle (MDLC) method. Thewriter intends to build a interactive learning media to stimulate the children basic knowledge that includes theintroduction of state as a teacher’s tool in delivery the materials. This i nteractive learning media consist of text,images, audio and 2D animation that designed as attracive as possible to increase the children curiosity so thatthe materials delivery becomes easier and enjoyable.This application is built using Adobe Photoshop, AdobeIllustrator and Unity 3D software. While for designing system writer use Unified Modelling Language (UML).The purpose of this study is to simplify and increase the desire to learn for elementary school children wherelearning will be made with a fun and attractive appearance. The final result of this research is the creation of aninteractive multimdia-based color recognition application for elementry school education as a subitute for theclassical learning method into a more effective learning method.